Previsão de consumo de água na estação de tratamento de água de Gravatá - PB - Silva, Nivaldo Antônio de Souza (2021)
The present thesis aims to predict the consumption in the Water Treatment Plant of Gravatá-PB.Through this research, we approached the water supply system, with its components, the water treatment plant, and the water supply system in Campina Grande.To predict water consumption, we use as a basis the main concepts related to time series, namely, the exponential smoothing algorithm and the Box- Jenkins models.These models show the integrated autoregressive models of ARIMA and ARIMAX moving averages. In ARIMAX we use independents variables.The independent variables used in ARIMAX were the estimate of the trend, the dummy variable, which represents the consumption of water in the period of the COVID- 19 pandemic, and the temperature of the Campina Grande region. Finally, we performed comparisons with the results obtained from the predictions and verified that the model ARIMAX (1,1,4) with the independent variable temperature of the Campina Grande region obtained better predictive result.